Accelerating a Bellman-Ford routing algorithm using GPU - Jeong, In-Kyu; Uddin, Jia; Kang, Myeongsu; Kim, Cheol-Hong; Kim, Jong-Myon (© 2014 Springer Verlag, 2016)
This conference paper was presented in the 2014 FTRA International Symposium on Frontier and Innovation in Future Computing and Communications, FCC 2014; Auckland; New Zealand; 13 January 2014 through 16 January 2014 [© 2014 Springer Science+Business Media Dordrecht] The conference paper's definite version is available at: :http://dx.doi.org/10.1007/978-94-017-8798-7_19